Confrontation and the Re-Privatization of Domestic Violence - Tuerkheimer, Deborah (2014)
When the Supreme Court transformed the right of confrontation in Crawford v. Washington, the prosecution of domestic violence predictably suffered as a result. But commentators at the time did not anticipate how the Court’s subsequent Confrontation Clause cases would utterly misconceive the nature of domestic violence, producing a flawed understanding of what constitutes a “testimonial” statement. Although the Court’s definition was especially problematic in the domestic violence context, its overly rigid approach finally became intolerable in Michigan v. Bryant, a 2011 case that did not involve domestic violence. In Bryant, the Court resurrected a public–private divide that relegated domestic violence to quasicriminal status, at best. By distinguishing between “domestic” and “nondomestic” disputes and minimizing the harms and dangers associated with the former, the Court revived long-standing hierarchies that were ostensibly repudiated decades ago. In assessing the significance of the Crawford revolution after ten years, I focus here on this largely unremarked jurisprudential move, which raises the distinct possibility that a privatized notion of domestic violence infected the Court’s reasoning even before Bryant